2019
DOI: 10.23838/pfm.2019.00128
|View full text |Cite
|
Sign up to set email alerts
|

White matter hyperintensities in migraine: a review

Abstract: Migraine is a neurological disorder characterized by recurrent spells of headache accompanied by brain symptoms such as nausea, vomiting, photophobia, and phonophobia. White matter hyperintensity (WMH) is the most frequent radiological abnormality observed in migraineurs. Older studies have reported that the prevalence of WMH is about 30% in migraineurs, while latest studies using advanced technology show that WMHs are present in about 70% of young (age < 50 years), vascular risk factor-free patients with migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…This suggests the pathophysiological mechanisms of ischemic change operating in subcortical WMH are different from those in the typical CVRFs. This pattern has been described in patients with migraine [47]. A possible explanation for this different clinical profile could be a relatively lower susceptibility of the most peripheral white matter to blood flow changes, given by the double blood supply of the juxtacortical white matter, in contrast to the centrum semiovale, which has a single blood supply [48].…”
Section: Discussionmentioning
confidence: 66%
“…This suggests the pathophysiological mechanisms of ischemic change operating in subcortical WMH are different from those in the typical CVRFs. This pattern has been described in patients with migraine [47]. A possible explanation for this different clinical profile could be a relatively lower susceptibility of the most peripheral white matter to blood flow changes, given by the double blood supply of the juxtacortical white matter, in contrast to the centrum semiovale, which has a single blood supply [48].…”
Section: Discussionmentioning
confidence: 66%
“…Small white matter lesions are commonly observed in patients with migraine and are typically identified as hyperintensities on MRI T2‐weighted and FLAIR sequences 50‐52 (Figure 1). The reported prevalence of WMH on MRI among those with migraine ranges widely, although more recently performed studies using modern MRI scanners and analysis techniques demonstrate a prevalence as high as 70% in people with migraine younger than 50 years of age and without vascular risk factors 53 …”
Section: Resultsmentioning
confidence: 99%
“…The reported prevalence of WMH on MRI among those with migraine ranges widely, although more recently performed studies using modern MRI scanners and analysis techniques demonstrate a prevalence as high as 70% in people with migraine younger than 50 years of age and without vascular risk factors. 53 The etiology of WMHs attributed to migraine is yet to be defined, but it is possible that they are a result of or a marker of pathophysiologic processes involved in migraine. Thus, the study of WMH could yield insights into migraine pathophysiology and potentially contribute to the development of migraine biomarkers, similar to other brain structural measures.…”
Section: White Matter Hyperintensities In Migrainementioning
confidence: 99%
“…However, as the prevalence of WMHs increases with age and comorbidities, the migraine-attributed increase in WMHs, if present, can be obscured by age-related changes. 19,20 Therefore, age and comorbidities should be considered in interpreting study results on WMHs in migraine. In addition, methodological parameters for the detection of WMHs, such as MRI resolution, definition of WMH, and manual counting vs. automated segmentation, can affect the results particularly in younger patients with very early stage of WMH development.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25] Several clinic-based studies have reported a high prevalence of WMHs in patients with migraine. Most studies reported that deep WMH is the predominant type of WMH in patients with migraine, 20 and recent studies using 3T with a slice thickness of <3 mm reported a high prevalence of WMHs of about 70% in young (aged <50 years) migraineurs without vascular risk factors. 6,26 In particular, deep WMH was the predominant type of WMHs in patients aged <50 years and without vascular risk factors.…”
Section: Deep Wmhs In Migrainementioning
confidence: 99%